The use of human acellular dermal matrices in advanced wound healing and surgical procedures: State of the art. Issue 4 (24th May 2021) - Tognetti, Linda; Pianigiani, Elisa; Ierardi, Francesca; Lorenzini, Guido; Casella, Donato; Liso, Flavio Giulio; De Pascalis, Andrea; Cinotti, Elisa; Rubegni, Pietro
Abstract: Wound closure after post‐traumatic injuries and/or localized at peculiar body sites (head‐and‐neck, oral cavity, legs) are particularly challenging and can often be delayed due to local and systemic factors. In case of deep wounds and/or hard‐to‐heal wounds, grafting of dermal acellular matrices (ADM) is often needed. Though a great variety of synthetic and semisynthetic dermal and skin equivalents are available, viable human dermis, is still considered the most physiological alternative to replace the loss of autologous dermis, by acting as a physiological scaffold that add structural support to soft tissues. To date, human ADMs (hADMs) have been employed in the reconstruction of skin defects affecting almost all body sites, ranging from visceral sites to the skin and subcutaneous tissues. This review aims to investigate the use of hADM at different body sites and their peculiar advantages. A literature search was using the search terms "acellular dermal matrices", "dermal regeneration", "advances wound healing", "human acellular dermal matrices surgery". A total of 50 out of 150 papers was included. Based on the current body if evidence, hADMs appear to bring several advantages, such as: protection of deep structures (eg, tendons, bones, cartilage and nerves); stimulation of a functional new dermis (rather than a scar); reduction of wound closure time; control of pain and exudate. Finally, hADMs may represent the best treatment option for hard‐to‐heal wound not only in terms of efficacy and patient satisfaction bout also in terms of sanitary costs, especially across Europe, where hADMs cannot be commercialized as medical devices.